2017
DOI: 10.1186/s12882-017-0718-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regional citrate anti-coagulation on the coagulation system in critically ill patients receiving continuous renal replacement therapy for acute kidney injury - an observational cohort study

Abstract: BackgroundRegional anticoagulation with citrate is the recommended first line treatment for patients receiving continuous renal replacement therapy (CRRT). There is wide variability in filter patency which may be due to differences in patient characteristics and local practice. It is also possible that citrate has effects on primary and secondary haemostasis, fibrinolysis and platelet function that are still unknown. The primary aim of the study is to describe the effect of citrate on coagulation and fibrinoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…We found that reduced systemic perfusion pressure was associated with development of AKI, confirming previous studies 25 , 26 . Further, a recent study of patients in the ICU found that abnormalities in renal and portal venous Doppler measurements were associated with major adverse kidney events 15 .…”
Section: Discussionsupporting
confidence: 92%
“…We found that reduced systemic perfusion pressure was associated with development of AKI, confirming previous studies 25 , 26 . Further, a recent study of patients in the ICU found that abnormalities in renal and portal venous Doppler measurements were associated with major adverse kidney events 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Also, we used widely available assays that could have been applied in this context if our results had suggested that monitoring citrate anticoagulation with them could be valuable. Lastly, the study took 2.5 years to complete and not all planned investigations were performed in all patients [ 17 ]. This reflects our very tight inclusion criteria and the challenges of studying coagulation biochemistry in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to commencing CRRT, blood was sampled from the patient's arterial line for measurement of full blood count (FBC) and clotting profile, including prothrombin time expressed as international normalised ratio (INR), activated partial thromboplastin time (APTT) expressed as activated partial thromboplastin time ratio (APTTr), Clauss fibrinogen, D-dimer and platelet function assay (PFA-100). Baseline assessment for hereditary and acquired coagulopathies was performed as previously described [ 17 ]. Plasma samples were stored at − 80 °C for subsequent batch testing of thrombin generation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation